The effect of 24-hour intraocular pressure fluctuation on glaucoma progression in primary angle closure glaucoma - A.Rahim @ Samsuddin, Haslinda (2015)
Introduction Primary Angle Closure Glaucoma (PACG) is a common glaucoma type in Asian population. Malays are among affected races in South East Asian with PACG prevalence of 0.12% to 2.5%. To date, intraocular pressure (IOP) is the only modifiable glaucoma risk factor. Two IOP subcomponents; the higher mean IOP and the wider IOP fluctuations are currently being looked upon as important predictors of glaucoma progression. Objectives To determine and compare the 24-hour overall mean IOP, mean IOP peak, mean IOP trough, and IOP fluctuation in progressed and non-progressed PACG. Methodology A cross-sectional study was conducted in Hospital Universiti Sains Malaysia, Kelantan involving 25 patients with 50 eyes diagnosed with PACG. They were grouped into progressed PACG (11 eyes) and non-progressed PACG (39 eyes). AGIS scoring system was used to determine the progression group. All patients were admitted for 24 hours period. Six IOP measurements were performed at 4-hour time points; at 0800, 1200, 1600, 2000, 2400, and 0400. Goldmann Applanation Tonometer (GAT) was used for all IOP measurements. Statistical analysis used were independent t test, Mann-Whitney U test, and Fisher’s exact test. Results Majority of progressed eye group of PACG exhibited patterns of night peak with afternoon trough, while non-progressed eye group showed patterns of morning peak with night trough. At 4-hour time points, the progressed eye group had lower mean IOP, mean peak IOP, and mean trough IOP but wider mean IOP fluctuation. Over 24 hour period, there was no significant difference for all IOP variables in both groups. The 24-hour mean overall IOP mean range was 13.7 to 15.3 mmHg (p = 0.202), overall mean IOP peak range was 17.0 to 18.0 mmHg (p = 0.285), overall mean trough range was 11.0 to 13.0 mmHg (p = 0.151), and overall mean IOP fluctuation was 6.0 mmHg (p = 0.803). Conclusion Progressed and non-progressed eye group of PACG demonstrated no significant difference in terms of all IOP variables over 24-hour period. Despite similar overall mean IOP fluctuation during 24-hour period, the progressed eye group had wider mean IOP fluctuation than the non-progressed eye group at 4-hour time points.